1955
DOI: 10.1139/p55-088
|View full text |Cite
|
Sign up to set email alerts
|

Radio Observations of the Ionosphere at Oblique Incidence

Abstract: A description is given of an automatic method of using the radio pulse technique at oblique incidence to investigate the structure of the ionosphere. Sweep frequency photographic records were taken for the path Ottawa–Saskatoon (2355 km.). The records obtained confirm the validity of the theory relating vertical incidence to oblique incidence propagation. Sweeps showing such phenomena as E layer cutoff, transmission of the Pedersen ray, multiple reflections, are shown. It is found that the F1 layer is the impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1956
1956
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Faraday rotation due to the geomagnetic field is non-reciprocal in this sense. The failure of the recriprocity for HF ionospheric paths has been reported in previous reports [13][14][15][16].…”
Section: Reciprocitysupporting
confidence: 66%
“…Faraday rotation due to the geomagnetic field is non-reciprocal in this sense. The failure of the recriprocity for HF ionospheric paths has been reported in previous reports [13][14][15][16].…”
Section: Reciprocitysupporting
confidence: 66%
“…Note that the current goes to zero at the ends of the antennas. The radiation fields generated by an antenna excited by the current described in Equations (1) and (2) are given by [5,6,13,14]:…”
Section: Expressions For the Current Distribution And The Electromagnmentioning
confidence: 99%
“…The radiation from short dipoles is generally studied to obtain information concerning the electromagnetic radiation generated by oscillating currents; the radiation from quarter-wave and half-wave dipoles tends to be studied for practical applications. Moreover, antennas of varying lengths with oscillating currents are used as receiving or transmitting antennas in many applications in atmospheric research, for example, in the study of electromagnetic wave transmission and reflection across the ionosphere [2]. They are also the receiving antennas of choice in VHF interferometric applications pertinent to the location of discharge activity inside thunderclouds [3].…”
Section: Introductionmentioning
confidence: 99%
“…The Canadian experiments [10,11] made over an east-west path of 2,350 km showed that under certain conditions the Pedersen ray was relatively important and that signals were sometimes received at frequencies up to 10 percent higher than the so-called "classical MUF". In these experiments, good agreement was found between the observed classical MUF's and the MUF's calculated on the basis of Sellmeyer theory.…”
Section: Survey Of Previous Workmentioning
confidence: 99%
“…During the war B eynon (4] extended these experiments to longer path lengths with improvemen ts in the recording technique. After World War II oblique-incidence work was extended to still greater distances in Germany (5 , 6, 7, 8, 9], Canada (10,11,12], the United States (13,14,15], and Japan (16]. I The results of these investigations will be considered in th e following section.…”
Section: Introductionmentioning
confidence: 99%